Deformation monitoring of typical composite structures based on terrestrial laser scanning technology. (15th October 2018) - Xu, Xiangyang; Yang, Hao; Neumann, Ingo
Abstract: Terrestrial laser scanning (TLS) technology plays an important role in the field of deformation monitoring nowadays, and a lot of the architectures are arched composite structures, which are required to be further understood for their mechanical and physical properties. Only a theoretical numerical analysis is sometimes difficult and defective to achieve, due to varying loads and other factors influencing the stability and reliability of such structures. Therefore, measurements can improve the theoretical analysis in several ways. One of the most important issues is the deformation analysis within load experiments. This paper focuses on the presentation of new possibilities for surface-based measurement techniques and their applicability in the deformation analysis of arched structures. The goal of this paper is to investigate the difference of load-displacement relationships between arched and beam structures though a static load experiment based on high accuracy TLS measurement techniques and the surface analysis method. In this paper, we try to reveal the influencing mechanism of 'prestressing-like' force and interpret why arched structures can withstand a surprisingly greater load than beam structures under the same conditions.